POTENSI SUMBER BIOGAS BERBASIS TINJA PADA SUATU CLUSTER PERUMAHAN - As zhu ra; Sudarti -; Yushardi - (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2021)
Abstract: THE POTENTIAL OF BIOGAS SOURCES BASED ON REFERENCE IN A HOUSING CLUSTER. In the future there will be a shortage of fuel oil, as a result developed countries will begin to work on the management of use in replacing the problem of low fuel oil and shortage of LPJ gas in the future, one of which is to produce alternative energy using human waste as the basic material, usually called Bio- Gas / Bio-Fuel. However, the management system and processes still use septic tanks that absorb human waste. So the main material or human waste that can be made to generate alternative energy for general public needs, so that it is not wasted using existing disposal methods. This activity is an explanatory activity to describe the process of disposing of human waste in the process of the exhaust pipe equipment system for each house by accumulating it in the central disposal area for the fermentation process to produce methane gas which is converted into gas power to electricity. This invention is used to find out how to make biogas from human waste. The findings of the present invention show the addition of methane gas and a central septic-tank in several households. Key words: Energy, Alternative, Biogas, Human waste, Fermentation process, Biofuel Abstrak: Pada masa depan akan terjaddi kekurangan bahan bakar minyak, akibatnya wilayah negara maju memulai mengerjakan pengelolaan digunakan dalam menggantikan permasalahan sedikitnya BBM dan kekurangan gas LPJ pada masa depan nanti, salah satu yang dilakukan adalah memproduksi energi alternative dengan bahan dasar kotoran manusia biasanya dinamakan dengan Bio-Gas/Bio-Fuel. Akan tetapi, system pengelolaannya dan prosesnya masih menggunakan septik-tank yang meresap kotoran manusia. Jadi bahan utama atau limbah manusia yang sepatutnya dapat dibuat untuk penghasilan tenaga alternative untuk keperluan umum masyarakat, supaya tidak terbuang sia-sia menggunakan cara pembuangan yang ada. Kegiatan ini merupakan pada kegiatan eksplanatori berbuat untuk mendiskripsikan proses prosedur membuang kotoran manusia dalam proses system perlengkapan pipa pembuangan tiap-tiap rumah dengan dikomulatifkan di wardah pembuangan pusat untuk proses fermentasi untuk menghasilkan gas metana yang dirubah dalam tenaga gas ke listrik. Penemuan ini digunakan untuk mengetahui bagaimana cara membuat biogas dari kotoran manusia. Perolehan dari penemuan ini memperlihatkan penambahan gas metana dan sentral septik-tank pada beberapa rumah tangga. Kata kunci: Energi, Alternatif, Biogas, Kotoran manusia, Proses fermentasi, Biofuel